(untitled) (AYUSHDHARA, 2020)
Background: Inflammation of the conjunctiva due to allergy is known as allergic conjunctiva. It is also seen in the people suffering from allergic rhinitis and is affected by all age groups at least once in their lifetime. But older population and children are more prone for allergic conjunctivitis. Objectives: To evaluate the effect of Aschyotana karma or the therapy with Bilvadi eye drops in the management of Vataja abhishyanda (allergic conjunctivitis). Design: This was an observational study with random sampling. Forty subjects who fulfilled the eligibility criteria were included for the study. Patients with complaints of Allergic Conjunctivitis were selected from OPD of Department of Shalakya Tantra (Netra-Roga), R.G.G.P.G. Ayu. Hospital Paprola, Himachal Pradesh. These patients were administered Bilvadi aschyotana 2 eye drops 4to 5 times for 15 days and were assessed for itching, redness, burning sensation and photophobia before the treatment, on the 3rd day, once in a week and after the treatment. Results: Aschyotana with Bilvadi eye drops in Vataja abhishyanda provided significant relief in itching 70.09%, redness 41.7%, burning sensation 47.6% and photophobia 53.3%.